A Molecular Tool for Facilitating Large Scale Seed Production and Genetic Purity Testing of White Onion Lines with High Total Soluble Solids - VIJAY MAHAJAN; PUTHEM ROBINDRO SINGH; DEEPANSHU JAYASWAL; KULDIP JAYASWALL (Seed Research, 2024)
Owing to the increasing demand from processing industries, there is a need to produce short-day white onion lines with high total soluble solids. Molecular markers, known for their high precision and reproducibility, are more reliable than morphological and biochemical markers for creating DNA fingerprints to test seed genetic purity and identify lines with elevated total soluble solids. Our individual bulb selection methods yielded short-day white onion lines which contain ≥ 18% TSS, which is low as per our requirement. Twenty SSR markers were utilized to characterize 19 short-day white onion lines derived from individual bulb selection till the eighth generation. The overall average number of alleles per simple sequence repeat locus, heterozygosity, and polymorphism information content were found to be 2.45, 0.54, and 0.44, respectively. A simple sequence repeats genotypingbased dendrogram separated all the lines into two clusters. Almost all of the lines in clusters IA and IB exhibit significant levels of total soluble solids, except sub-group IAb-I, which contains modest levels. Our study revealed that AcB-Shweta-tss-9.8 (total soluble solids -9.8%) & HT-GR-1A-M-7TSS>18_21.0 (total soluble solids - 21.0%) are more diversified based on the dendrogram and heat map generated by genotyping and total soluble solids data, respectively. These high total soluble solids containing lines would be extremely advantageous for accelerating molecular breeding of short-day, high total soluble solids containing white onion development using marker- assisted selection. Furthermore, these markers could expedite the selection of bulbs with high total soluble solids (HTSS) content for large-scale seed production and facilitate effective genetic purity testing of seeds.